Mekanisme Perkembangan Pasar Modal Sebagai Salah Satu Produk Investasi di Masyarakat - Sinta Ayu Purnamasari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The capital market is one of the important instruments in the economy that functions to connect parties in need of funds with those who have funds through the buying and selling of securities. As an investment product, the capital market plays a strategic role in driving economic growth, creating job opportunities, and increasing the efficiency of resource allocation. The aim of this study is to analyze the mechanisms of the capital market and its development as an investment product in society. This study also aims to identify the functions of the capital market in the economy and assess its impact on the general economic condition of society. The research method used in this study is a descriptive approach with qualitative analysis of secondary data obtained from various sources, such as annual reports from financial institutions and related literature. The results show that the capital market functions as a means of raising funds, distributing risks, and providing transparent information. In addition, the development of the capital market has made significant progress, with increased participation from the public in investing in stocks and bonds. This study also found that with the existence of the capital market, the public has greater opportunities to invest, which ultimately leads to the improvement of overall economic welfare.